Regulation of tumor angiogenesis by the crosstalk between innate immunity and endothelial cells - Ebeling, Svenja; Kowalczyk, Anita; Perez-Vazquez, Diego; Mattiola, Irene (Frontiers in Oncology, 2023)
Endothelial cells and immune cells are major regulators of cancer progression and prognosis. Endothelial cell proliferation and angiogenesis are required for providing nutrients and oxygen to the nascent tumor and infiltration of immune cells to the tumor is dependent on endothelial cell activation. Myeloid cells and innate lymphocytes have an important role in shaping the tumor microenvironment by crosstalking with cancer cells and structural cells, including endothelial cells. Innate immune cells can modulate the activation and functions of tumor endothelial cells, and, in turn, endothelial cell expression of adhesion molecules and secretion of inflammatory mediators can affect immune cell extravasation and activation. However, the mechanisms underlying this bidirectional crosstalk are not fully understood. In this review, we will provide an overview of the current knowledge on the pathways regulating the crosstalk between innate immune cells and endothelial cells during tumor progression and discuss their potential contribution to the development of novel anti-tumor therapeutic approaches.